2022
DOI: 10.3389/fphar.2022.794405
|View full text |Cite
|
Sign up to set email alerts
|

The TCM Preparation Feilike Mixture for the Treatment of Pneumonia: Network Analysis, Pharmacological Assessment and Silico Simulation

Abstract: The Feilike mixture (FLKM) is a valid prescription that is frequently used to assist in the clinical treatment of pneumonia. However, the mechanisms of its effects remain unclear. First, through literature evaluation, it was preliminarily determined that FLKM improved clinical symptoms, regulated immune inflammation response and ameliorated pulmonary function. Then, via database search and literature mining, 759 targets of the 104 active compounds of FLKM were identified. The component-target (CT) network show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A randomized controlled trial discovered that HXZQ dropping pills and LHQW granules combined with CWM may have clinical benefits for improving clinical symptoms of COVID-19 patients, lowering anti-infective drug utilization, and improving patient prognosis [ 9 ]. FLKM has been shown in animal studies to alleviate pathological lung tissue injury, reduce neutrophil infiltration in rats with LPS-induced pneumonia, and alleviate clinical symptoms and signs in patients with pneumonia [ 10 ]. PDL protects against LPS-induced respiratory inflammation in mice [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial discovered that HXZQ dropping pills and LHQW granules combined with CWM may have clinical benefits for improving clinical symptoms of COVID-19 patients, lowering anti-infective drug utilization, and improving patient prognosis [ 9 ]. FLKM has been shown in animal studies to alleviate pathological lung tissue injury, reduce neutrophil infiltration in rats with LPS-induced pneumonia, and alleviate clinical symptoms and signs in patients with pneumonia [ 10 ]. PDL protects against LPS-induced respiratory inflammation in mice [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has proven that AKT and IL-6 are important targets for the treatment of pneumonia [ 17 , 18 , 55 ]. It has been reported that lobar pneumonia and bronchial pneumonia patients have elevated IL-6 levels relative to those without pneumonia [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology is a comprehensive approach that generates information that can be used to identify drugs with pleiotropic mechanisms [ 16 , 17 ]. It is popularly used to screen potential bioactive compounds, discover targets, and explore the mechanisms of TCMs in biomolecular networks [ 18 ]. Molecular docking [ 19 ] and dynamics simulation [ 20 ] are important technical means used to explore potential active candidate compounds in TCM.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled trial found that HXZQ dropping pills and LHQW granules combined with CWM may have clinical advantages for improving the clinical symptoms of COVID-19 patients, reducing the utilization rate of antiinfective drugs, and improving patient prognosis [9]. Studies in animals have shown that FLKM ameliorates pathological injury of lung tissue, reduced neutrophil in ltration in rats with LPS-induced pneumonia, and alleviated clinical symptoms and signs in patients with pneumonia [10]. PDL protects against LPS-induced respiratory in ammation in mice [11].…”
Section: Discussionmentioning
confidence: 99%